Toeic training listening comprehension 370 - Jim, Lee (Thời đại; Công ty TNHH Nhân Trí Việt, 2011)
Dùng chung cuốn Toeic training listening comprehension 730; Đáp án cuốn Toeic training listening comprehension 730